2011
DOI: 10.1007/s00167-011-1461-9
|View full text |Cite
|
Sign up to set email alerts
|

Can patients really participate in sport after high tibial osteotomy?

Abstract: Therapeutic study, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 39 publications
5
71
1
4
Order By: Relevance
“…Mancuso et al [59] found that only 30% of patients undergoing TKA expressed motivation to RTS, whereas Saragaglia et al [35] found that 71% of patients undergoing HTO were motivated to RTS but that neither the motivation nor the pre-existent sport level was related to greater RTS. In contrast, Bonnin et al [43] found a correlation between patient motivation and activity level, with motivated patients being more active postoperatively. These contrasting findings may be explained by the nature of the practiced sports.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Mancuso et al [59] found that only 30% of patients undergoing TKA expressed motivation to RTS, whereas Saragaglia et al [35] found that 71% of patients undergoing HTO were motivated to RTS but that neither the motivation nor the pre-existent sport level was related to greater RTS. In contrast, Bonnin et al [43] found a correlation between patient motivation and activity level, with motivated patients being more active postoperatively. These contrasting findings may be explained by the nature of the practiced sports.…”
Section: Discussionmentioning
confidence: 94%
“…The influence of patient motivation was mentioned in four studies. Bonnin et al [43] found motivation to be strongly correlated to RTS, whereas Saragaglia et al [35] found no correlation. The preoperative sports level was mentioned as a confounder in six studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the knee function expectations of that group are not very high [11] . In contrast, patients who are good candidates for a knee function preservation approach such as meniscal repair, meniscal transplantation, chondroplasty, or osteotomy [19] tend to have greater expectations to be able to continue impact sport, recreational or vocational activities. They also tend to be more willing and better able to implement significant behavioral changes, to develop the support systems needed for their maintenance, are willing to tolerate and live with minor-to-moderate intermittent knee pain and are willing to learn to become more pain tolerant.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of DFO and PTO in treating incipient unicompartmental osteoarthritis of the knee has been questioned, especially after the advent of unicompartmental knee replacement. Today, knee osteotomies are primarily used to treat incipient to moderate unicompartmental knee osteoarthritis in younger and active patients [15] who wish to resume high intensity sporting activities [4]. The popularity of knee osteotomies has fluctuated as changes in technique and results have been reported.…”
mentioning
confidence: 99%